Long story encrypted in a small grain – zircon from meta-andesite in the Lower Köli Nappes reveals a complex history of the Virisen Arc Terrane, Scandinavian Caledonides, Sweden - Walczak Katarzyna A.; Włodek Adam; Cuthbert Simon; Carter Isabel S. M.; Ziemniak Grzegorz (Mineralogia, 2025)
This short report presents the investigation results on the zircon from meta-andesitic rock from the Ankarede Volcanite Formation of the Lower Köli Nappe Complex in Scandinavian Caledonides. Previous U-Pb dating revealed a wide span of dates ranging from ca. 520 to ca. 480 Ma, with a mean age of 491 ± 3 Ma for the zircon cores. Using cathodoluminescence and back-scattered electron imaging, along with chemical mapping, we identified distinct zones within the zircon grains; 1) cores of clear magmatic provenance, 2) mantles also of magmatic origin but with a slightly different chemical composition and 3) zircon rims that suffered metamictisation and fluid-induced alterations. These findings highlight a complex growth history and alteration of studied zircon that affect the interpretation of zircon dating results. This research underscores the importance of detailed zircon studies for understanding the intricate processes involved in the magmatic and metamorphic evolution of Virisen terrain in Scandinavian Caledonides.